PENGARUH PEMBELAJARAN MODEL TPSR (TEACHING PERSONALITY AND SOSIAL RESPONSIBILITY) TERHADAP BERFIKIR KREATIF DAN TANGGUNG JAWAB PADA MATA KULIAH EVALUASI PENDIDIKAN - Siregar, Fajar Sidik; Siregar, Arifin; Sagala, Ramlan Sahputera; Abady, Andi Nur (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
This study aims to determine the influence of learning the TPSR (Teaching Personality And Social Responsibility) Model on creative thinking and student responsibility of the PGSD Study Program Education Evaluation Course FIP UNIMED. The type of research conducted is a type of experimental research. This research design uses pre-test & post test design. The location of the research was carried out in the PGSD FIP Unimed study program. The sample of this study amounted to 40 students. Data collection techniques in this study use research instruments in the form of questionnaires that have been compiled and validated by experts. The results showed that the personal teaching and social responsibility learning model has an influence on students' creative thinking, namely the significance value is 0.000. In addition, the TPSR learning model also has an influence on student responsibility, namely the significance value is 0.006.